CHARACTERISTIC FEATURES OF THE COURSE OF CITOMEGALOVIRUS INFECTION IN CHILDREN - Mukhtorova Shokhida Abdulloevna (Galaxy International Interdisciplinary Research Journal, 2023)
Cytomegalovirus (CMV) is a common viral infection that can cause a range of clinical manifestations in children. This article aims to describe the characteristic features of CMV infection in children. The study was conducted by reviewing relevant literature sources, including scientific articles and textbooks. The article outlines the methods used to identify CMV infection in children, including laboratory tests, clinical examination, and imaging studies. The results section describes the clinical manifestations of CMV infection in children, including neurological, gastrointestinal, and respiratory symptoms. The discussion section discusses the pathophysiology of CMV infection and the risk factors associated with severe disease. The article concludes that CMV infection is a significant cause of morbidity and mortality in children, particularly in immunocompromised individuals. Early diagnosis and appropriate management are crucial in preventing severe disease outcomes.